Prevalence of malocclusion and orthodontic treatment needs among down syndrome sudanese individuals - Ibrahim, Hiba A; Abuaffan, Amal H (Brazilian Dental Science, 2015)
Objective: To determine the prevalence of malocclusion and orthodontic treatment needs in Sudanese’s Down syndrome individuals in Khartoum area. Material and Methods: A total of 75 (37 males and 38 females) Down syndrome individuals age ranging from 6-28 years of age, were clinically examined after obtaining their guardian’s consent. Malocclusion was determined based on Angle and Incisor classification of malocclusion. The data were analysed and presented in tables using the Statistic Package for social sciences (SPSS) program version17 descriptive statistic, Frequency distribution tables and graph were utilized to perform the results. Results: Angle Class III malocclusion (58.7%) and Incisor III malocclusion (53.3%) represents the most prevalent types of malocclusions. Angle class III malocclusion was more frequent among females (60.5%) than males (56.8%).The majority of individuals with Down syndrome are in great need for orthodontic treatment (85.3%). Conclusion: The prevalence of malocclusion and orthodontic treatment need among Sudanese Down syndrome individuals was high.  Angle and Incisor class III malocclusions represent the commonest trait of malocclusion and reported more frequency in females than males. Orthodontic treatment for Down syndrome individual should be multidisciplinary in order to conservative superior treatment pattern. Keywords: Down syndrome; Class III malocclusion; Orthodontic treatment.